Mapping Christian rhetorics : connecting conversations, charting new territories - DePalma, Michael-John, 1977-; Ringer, Jeffrey M., 1976- (Routledge studies in rhetoric and communication., 2015)
"The continued importance of Christian rhetorics in political, social, pedagogical, and civic affairs suggests that such rhetorics not only belong on the map of rhetorical studies, but are indeed essential to the geography of rhetorical studies in the twenty-first century. This collection argues that concerning ourselves with religious rhetorics in general and Christian rhetorics in particular tells us something about rhetoric itself--its boundaries, its characteristics, its functionings. In assembling original research on the intersections of rhetoric and Christianity from prominent and emerging scholars, Mapping Christian Rhetorics seeks to locate religion more centrally within the geography of rhetorical studies in the twenty-first century. It does so by acknowledging work on Christian rhetorics that has been overlooked or ignored; connecting domains of knowledge and research areas pertaining to Christian rhetorics that may remain disconnected or under connected; and charting new avenues of inquiry about Christian rhetorics that might invigorate theory-building, teaching, research, and civic engagement. In dividing the terrain of Christian rhetorics into four categories--theory, education, methodology, and civic engagement--Mapping Christian Rhetorics aims to foster connections among these areas of inquiry and spur future collaboration between scholars of religious rhetoric in a range of research areas."--Provided by publisher